Free Flap Elevation Times in Head and Neck Reconstruction Using the Harmonic Scalpel Shears. Issue 5 (May 2016) - DeSerres, Joshua J.; Barber, Brittany R.; Seikaly, Hadi; Harris, Jeffrey R.; O'Connell, Daniel A.
Abstract : Summary: Free tissue transfer has become the mainstay of head and neck cancer (HNC) reconstructive surgery. The objective of the study is to examine the efficacy of the Harmonic Scalpel (HS) Shears on free flap elevation time and complication rates after HNC reconstruction compared with traditional electrocautery. A retrospective review of 215 HNC patients undergoing surgical ablation and free flap reconstruction from January 2010 to April 2013 at the University of Alberta Hospital was undertaken. All patients requiring free flap reconstruction with radial forearm free flap or fibula free flap were included. Overall, there was no significant difference demonstrated between the HS and electrocautery groups for free flap elevation time for RFFFs ( P = 0.563) or FFFs ( P = 0.087). No differences were observed in donor-site complications. The HS is a reliable, safe, and alternative method of free flap elevation in HNC reconstructive surgery.